Ticks infesting birds in Atlantic Forest fragments in Rio Clam, State of Sao Paulo, Brazil - Sanches, Gustavo Seron [UNESP] (2012)
In the present study, we report tick infestations on wild birds in plots of the Atlantic Forest reforested fragments with native species and plots reforested with Eucalyptus tereticornis in the municipality of Rio Claro, State of Sao Paulo, Brazil. A total of 256 birds were captured: 137 individuals of 33 species, in planted native forest; and 128 individuals of 37 species, in planted Eucalyptus tereticornis forest. Nymphs of two tick species were found on the birds: Amblyomma calcaratum and Amblyomma longirostre, the former was more abundant in the fragments reforested with Atlantic forest native species, and the latter in the fragment reforested with E. tereticornis. New host records were presented for A. calcaratum.